九州西方海域産小型歯鯨類の研究―14 : 東支那海済洲島の南方海域で捕獲されたハセイルカについて - Takemura, Akira; Yoshida, Kazumoto; Mizue, Kazuhiro (長崎大学水産学部, 1967)
Delphinius sp., which is called HASE IRUKA (Hase dolphin) in Nagasaki, Japan, live in the west sea area of Kyushu. The authors investigated whether or not that dolphin is identified with SIEBOLD's dolphin or Delphinus capensis, and is different from Delphinus delphis. As the result of the investigation on the body color, external proportion, and skull measurement, it was proved that Hase dolphin is identical to CGAWA's Delphinus capensis and it was presumed that SIEBOLD's dolphin is this species. But it is unknown if Hase dolphin is identical to TRUE's Delphinus capensis which was caught in the coastal sea of the Cape of Good Hope. 長崎大学水産学部研究報告, v.24, pp.39-53; 1967 departmental bulletin paper